Appropriating live televised football through talk - Gerhardt, Cornelia (Studies in pragmatics, 2014)
Video-recordings of families and groups of friends watching the FIFA men's football World Cup in their homes allow access to the empirical rather than the imagined or inscribed audiences of a major television event. Qualitative analyses reveal how natural audiences behave in the reception situation appropriating live televised football through talk. Gerhardt shows how the mainly English television viewers use an array of linguistic and embodied resources to turn watching football into a meaningful activity in their groups. Cohesive devices and sequentiality link the fans' talk-in-interaction to the televised text (commentary and pictures). Gaze behaviour, pointing, and even jumping up and down are used as resources for a variety of functions like the construction of an identity as football fan.